THE LOWER PERMIAN IN THE OROBIC ANTICLINE (SOUTHERN ALPS, LOMBARDY): A REVIEW BASED ON NEW STRATIGRAPHIC AND PETROGRAPHIC DATA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2001)
Facies mapping at the 1: 10.000 scale of the Lower Permian in the Orobic Anticline, carried out in the framework of the CARG Project, allowed reconstruction of the basin architecture and refined subdivision of the stratigraphic succession with respect to the available framework. Paroxysmal effusion of benmoreites in the lower volcanic member of the Collio Formation was followed by a synsedimentary, polymodal volcanic activity (mugearite flows to rhyolite tuffs) during deposition of the overlying arenaceous-volcaniclastic member. After progradation of the Ponteranica Conglomerate proximal fan-delta facies, a possible marine transgression is suggested by rare foraminifers, newly found in the upper arenaceous-pelitic member of the Collio Formation. Magmatic evolution fits into a palaeogeodynamic scenario of continental wrenching; lack of rhyolites in the lower volcanic member points to distinct and/or non-coeval volcanic activity at the western edge of the Collio Basin (Orobic Anticline) with respect to the central-eastern sector (Trabuchello-Cabianca to Camuna Anticlines). Sandstone petrography, indicating provenance from overwhelming neovolcanic sources, is fairly uniform both vertically and laterally, and thus suggests high sedimentation rates for the Collio Formation, in agreement with the shorter time span recently assigned to this unit by radiometric data from the Camuna Anticline. Different sandstone composition in the Orobic and Camuna Anticlines is another line of evidence against physical continuity of the Collio Basin.